PENGARUH PARTISIPASI ANGGARAN DAN AKUNTANSI PERTANGGUNGJAWABAN TERHADAP KINERJA PEGAWAI KANTOR BPKAD KOTA PALOPO - Annisa, Annisa; Ramadhan, Abid; Suardi, Ahmad (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2022)
This study aims to determine the effect of budegetary participation and accountability on employee performance at the BPKAD office Palopo City. This study uses primary data as many as 40 sampels with the sampling method using total sampling. Data collection is done through a questionnaire with the help of the SPSS 23 application. Based on the test results show that budget participation has a significant effect on employee performance while accountability accounting has a significant effect on employee performance.